High intrinsic biosorption efficiency of cattle manure on Cr(VI): a potential low-cost fibre-rich biosorbent - Yap, Kwai Ling; Lee, Choon Min; Gan, Yee Lin; Tang, Teck Kim; Lee, Y. Y.; Tee, Tuan Poy; Lai, Oi Ming (Universiti Putra Malaysia Press, 2018)
Fibre-rich manure derived from grass-fed cattle showed significantly higher intrinsic sorption efficiency on Cr(VI) solution as compared to corncob, sawdust and cogon grass. This observation could be attributed to the ligneous nature and rough surface morphology of the cattle manure. Four-factor, three-level, face-centred composite design (FCCD) suggested the process was greatly affected by initial pH of the solution, contact time and sorbent dosage (p<0.0001), while stirring rate had negligible effect. Highest percentage removal (=70%) happened at pH 1-1.56, 0.79-1 g sorbent and 57-300 min contact time in 200 mg/L Cr(VI) solution. The process is spontaneous, endothermic and best described by pseudo-second-order and Langmuir model. It was found that adsorbed Cr(VI) could be recovered and CM could be reused at least three times with >50% adsorption efficiency. It is predicted that both physisorption and chemisorption are involved in the sorption process.